Dissolution of donor-vacancy clusters in heavily doped n-type germanium. (22nd December 2020) - Prucnal, Slawomir; Liedke, Maciej O; Wang, Xiaoshuang; Butterling, Maik; Posselt, Matthias; Knoch, Joachim; Windgassen, Horst; Hirschmann, Eric; Berencén, Yonder; Rebohle, Lars; Wang, Mao; Napoltani, Enrico; et al.
Abstract: The n-type doping of Ge is a self-limiting process due to the formation of vacancy-donor complexes (D n V with n ⩽ 4) that deactivate the donors. This work unambiguously demonstrates that the dissolution of the dominating P4 V clusters in heavily phosphorus-doped Ge epilayers can be achieved by millisecond-flash lamp annealing at about 1050 K. The P4 V cluster dissolution increases the carrier concentration by more than three-fold together with a suppression of phosphorus diffusion. Electrochemical capacitance–voltage measurements in conjunction with secondary ion mass spectrometry, positron annihilation lifetime spectroscopy and theoretical calculations enabled us to address and understand a fundamental problem that has hindered so far the full integration of Ge with complementary-metal-oxide-semiconductor technology.